A study of student readiness in blended learning using the disruptive innovations theory / Rashidah Abdul Razak - Abdul Razak, Rashidah (2016)
The rapid pace of technological development which have the fast pace of change had influence on every aspect of education especially in higher institution. The usage of information and communication technology (ICT) has widely been accepted and implemented particularly in blended learning using the disruptive innovation theory. Blended learning defined as an innovation of learning and teaching using the digital media and computer technology that enable the information to be transmitted via networks towards assisting, simplifying, boosting and accelerating the educational processes and can be accessed regardless of time and places. This study fundamentally used UTAUT2 model and based on disruptive innovation theory to understand well of blended learning. Hence this study aims to identify the relationship between the factors (performance expectancy, effort expectancy, social influence, facilitating condition, price value, habit and hedonic motivation) and readiness to use blended learning among 250 students of Universiti Teknologi MARA (UiTM). A survey was conducted and the data was analyzed using SPSS. The finding indicates that performance expectancy, price value and habit were significant to student's readiness in using blended learning technologies. For future study this research recommends to explore comparison between private and local university's students on readiness to use blended learning. It is recommended also for future research to focus on university or faculties which have implemented any of the disruptive blended learning's model for further and details research on disruptive innovation in the context of education.